New approaches to management of neonatal hypoglycemia - Rozance, Paul J. (Matern Health Neonatol Perinatol, 2016)
Despite being a very common problem after birth, consensus on how to manage low glucose concentrations in the first 48 h of life has been difficult to establish and remains a debated issue. One of the reasons for this is that few studies have provided the type of data needed to establish a definitive approach agreed upon by all. However, some recent publications have provided much needed primary data to inform this debate. These publications have focused on aspects of managing low blood glucose concentrations in the patients most at-risk for asymptomatic hypoglycemia—those born late-preterm, large for gestational age, small for gestational age, or growth restricted, and those born following a pregnancy complicated by diabetes mellitus. The goal of this review is to discuss specific aspects of this new research. First, we focus on promising new data testing the role of buccal dextrose gel in the management of asymptomatic neonatal hypoglycemia. Second, we highlight some of the clinical implications of a large, prospective study documenting the association of specific glycemic patterns with neurodevelopmental outcomes at two years of age.